The Variation of Address Terms Used by Family of Puri Agung Singaraja and Their Interlocutors in Their Daily Communications - Dewi, Komang Yuli Trisna (Universitas Pendidikan Ganesha, 2011)
This present study aimed at identifying variants of address terms used by family of Puri Agung Singaraja and their interlocutors in their daily communication. This study was a descriptive study whose objective was to describe the characteristics of particular sample or individual or other phenomena. The subject of this study were the family of Puri Agung Singaraja. In collecting the intended data, the researcher used two instruments namely tape recorder which was used to record conversations and note book used to note various situation or context in which the conversations took place. The result of this study shows that there are ten variations of address terms used by the family of Puri Agung Singaraja. The variation ranges from addressing a father, a mother, brothers and sisters, uncles and aunts. The variations take place as a result of the influence of types of social relations between the speakers and the interlocutors.